MISKONSEPSI TEOREMA PHYTAGORAS PADA BUKU AJAR SISWA SEKOLAH MENEGAH PERTAMA DENGAN PERBANDINGAN YANG BENAR - Christine Amori Damanik; Reka Bayu; Intan Novita Sari Simanullang; Sabam Isay Sianipar; Wingston Leonard Sihombing (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze misconceptions of the Pythagorean Theorem found in the Grade VIII Junior High School/Islamic Junior High School Mathematics textbook (Kemdikbud, 2022) and to compare them with the correct mathematical concepts. The research method used is qualitative with a content analysis approach, in which data were collected through document review of concept explanations, illustrations, examples, and exercises related to the Pythagorean Theorem. The results of the study reveal potential misconceptions, including the assumption that the Pythagorean Theorem applies to all types of triangles, a lack of clarity in identifying the hypotenuse as the longest side opposite the right angle, and students’ tendency to memorize Pythagorean triples without understanding the mathematical logic behind them. Comparison with the correct concepts shows that these misconceptions stem from insufficient conceptual emphasis, limited use of illustrations, and examples that focus more on procedures than on understanding. These findings indicate the need for improvements in the presentation of textbook material by adding emphasis on the conditions of right-angled triangles, the definition of the hypotenuse, and detailed explanations of Pythagorean triples. Thus, this study is expected to provide input for teachers and textbook authors in designing more conceptually oriented mathematics instruction, so that students’ understanding of the Pythagorean Theorem becomes more accurate and in-depth.